Social Work Research and Mixed Methods: Stronger With a Quality Framework - Foote, Lori A. (Research on social work practice, 2025)
Mixed methods are a useful approach chosen by many social work researchers. This article showcases a quality framework using social work examples as practical guidance for social work researchers. Combining methodological literature with practical social work examples, elements of a high-quality approach to mixed methods are showcased in this article. Specific components of a quality framework are used to ground the discussion. This framework helps researchers attend to important aspects of a mixed methods project's design, particularly as related to integration. Additional resources are provided for those interested in further deepening their mixed methods capabilities. Attending to components within this quality framework will help the researcher or consumer of research to think carefully about how the design helps to maximize the benefits that can be achieved by taking a mixed methods approach.